Rotating Flows Driven by Axisymmetric Blades in a Cylinder - Jae Won Kim (International Journal of Rotating Machinery)
A study is made of steady state flow of a viscous fluid, driven by a rotating endwall disk having radial blades in a finite geometry. Numerical solutions to the Navier-Stokes equations are obtained for the flows in the cylindrical cavity. The bottom endwall disk of the vessel is impulsively rotating at a constant rotating speed ft with respect to the longitudinal axis of it. Details of the three components velocity field are examined at high Reynolds number for its engineering application. The main parameter for this study is the number of the radial blades of a rotating pulsator. The numerical results for the fluid flows and pressure distribution, for both an odd and an even number of the blades are procured. The present output offers an optimal number of the blades for rotating machinery such as agitator. The grid-net for the numerical computation is constructed on a body-fitted coordinate system transformed from physical coordinates. It is also flexible to suit any number of blades attached on the rotating bottom disk. The algorithm for the numerical computation is based on the SIMPLE release by Patankar, and the results are validated with prior published data. In addition, a characteristic model is prepared for the pressure measurement. The pressure measurements performed for the present model are consistent with this computational work. The explicit effect of the blade on the overall flow character is scrutinized. The numerical data are processed to describe the behavior of the meridional velocities under different blade conditions. Also, the traces of particles are plotted to assess the effects. Pronounced differences are noted and these results supply comprehensive data for practical application.